Temporal Bone Resection for Squamous Cell Carcinoma of the Lateral Skull Base: Systematic Review and Meta‐analysis. (26th January 2023) - McCracken, Matthew; Pai, Kavya; Cabrera, Claudia I.; Johnson, Benjamin R.; Tamaki, Akina; Gidley, Paul W.; Manzoor, Nauman F.
Abstract: Objective: Temporal bone squamous cell carcinoma (TBSCC) is rare and often confers a poor prognosis. The aim of this study was to synthesize survival and recurrence outcomes data reported in the literature for patients who underwent temporal bone resection (TBR) for curative management of TBSCC. We considered TBSCC listed as originating from multiple subsites, including the external ear, parotid, and external auditory canal (EAC), or nonspecifically from the temporal bone. Data Sources: PubMed, Cochrane Library, Embase, and manual search of bibliographies. Review Method: A systematic literature review conducted in December 2020 according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Results: Survival data were collected from 51 retrospective studies, resulting in a pooled cohort of 501 patients with TBSCC. Compared to patients undergoing lateral TBR (LTBR), patients undergoing subtotal (SBTR) or total (TTBR) TBR exhibited significantly higher rates of stage IV disease ( P < .001), positive surgical margins ( P < .001), facial nerve involvement ( P < .001), and recurrent disease ( P < .001). A meta‐analysis of 15 studies revealed a statistically significant 97% increase in mortality in patients who underwent STBR or TTBR. On multivariate analysis, recurrent disease was independently associated with worse overall survival ( P < .001). On univariate analysis, facial nerve involvement was also associated with decreased overall survival ( P < .001). Conclusion: Recurrent disease was associated with risk of death in patients undergoing TBR. Larger prospective multi‐institutional studies are needed to ascertain prognostic factors for a wider array of postoperative outcomes, including histology‐specific survival and recurrence outcomes.